(untitled) (Bangladesh Journal of Child Health, 2022)
Introduction: Dyslipidemia increases the frequency and severity of micro and macrovascular complications of type 1 diabetes (T1D). Materials & Methods: This cross-sectional study was aimed to evaluate the frequency of dyslipidaemia and its association with other risk factors in children and adolescents with type 1 diabetes. A total of 397 Type 1 diabetes (T1DM) patients aged 10-18 years who attended, Paediatric diabetes clinic in BIRDEM over one year period were included in this study. Results: The overall frequency of dyslipidaemia was 63.5% and median duration of diabetes was 3.0[2.0- 5.0 years]. The High LDL was most cmmmon dyslipidaemia (81%) in our study population. FBS was significantly higher 12.8[10.0-15.5] vs 10.8[7.7- 12.6] (p<0.0001)) and higher median HbA1c 9.9 [8.5-11.9] vs 9.0[7.9-10.5] (p<0.0001)) was found in dyslipidaemic patients. Median systolic blood pressure was higher (110 vs100) in dyslipidaemic patients ( p =.042). Conclusion: The frequency of dyslipidemia was high among the children and adolescents with T1DM which was associated with poor glycaemic control. Our results provide strong support for prior literature in emphasizing the importance of good glycemic control, to reduce the risk of dyslipidaemia. BANGLADESH J CHILD HEALTH 2021; VOL 45 (2) : 79-82